Sistem Rekomendasi Pemilihan Basic Skincare Menggunakan Metode Content Based Filtering - Viona Putri Ardiana; Vihi Atina; Nurmalitasari Nurmalitasari (Universitas Islam Raden Rahmat, Malang, 2024)
Kumara Store offers a diverse range of cosmetics and skincare products in Mandan, Sukoharjo. Due to the extensive variety of products, customers frequently find it challenging to select basic skincare items. To address this issue, developing a recommendation system is crucial to assist customers in finding the most suitable products. This study employs the Content-Based Filtering method alongside the Rapid Application Development approach. The system features include product search and viewing capabilities, with recommendations being generated for users. Admin features allow for the management of attributes and data related to basic skincare products. The Content-Based Filtering technique recommends similar products based on their features or attributes. With 35 product samples and 6 attributes examined, the product Emina MS Pimple achieves the highest similarity score of 0.694 and will be recommended as a basic skincare product. This research can provide a foundation for future studies aimed at enhancing accuracy.